Young indigenous migrants in the Alameda Central. Peaceful disputes over the public space - Marcela Meneses Reyes (Iztapalapa, 2015)
This article seeks to explain the way that young indigenous migrant’s newcomers to Mexico City used, disputed and mean place into the public space. The analysis is focus on the data of ethnographic work on the Alameda Central and surrounding areas before and after the urban renewal project in 2012. The findings suggest that despite attempts by displacement, the young people studied deployed different Strategies in order to gain a foothold in the spaces that have appropriated and thereby legitimize their presence in the city.